(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Haematological tests have an important role in early diagnosis of the COVID-19 patient’s disease condition, considering the information they provide to physicians regarding the inflammatory process. This information includes leukocyte count and characteristics such as neutrophil or lymphocyte-dominance, inflammation (CRP) Serum ferritin and coagulation profile (D-dimer). Aim of this study was to investigate the association of hematological parameters with severity of the disease and identify the association of magnitude of any cytopenia and pancytopenia with the severity of COVID-19 patients. Materials and methods: This prospective observational study was conducted at dedicated COVID unit of Chattogram Maa O Shishu General Hospital from March 2021 to August 2021. A total of 100 RT-PCR(+ve) COVID cases were included in this study. Automated hematology analyzer was used to determine complete blood count (Total WBC count, absolute and relative count of each WBC type, RBC, and platelet count). Results: Majority patient were female (61%). Among all patient 87% patients were above 35 years of age. Patient with mild disease were comparatively younger than patient with severe disease. Major presenting complaints were cough (88%) shortness of breath (60%) fever (59%) sore throat (30%) and fatigue (26%). Raised pulse and respiratory rate were seen according to disease severity. Total WBC (p=0.0038) Neutrophil (p=0.0001) serum ferritin (p=0.0205) CRP (p=0.0004) and Ddimer (p=0.0004) were significantly increased in severe group and the patient with critical condition. No statistically significant difference was seen in the median value of platelet count (p=0.4364). Conclusion: Leukocytosis, Neutrophilia, elevated serum ferritin, CRP and D-dimer are significantly increased in patients with severe and critical disease condition of COVID-19 patient. Lymphopenia also featured in these patients, which is associated with the severity of disease. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 8-13